2014
DOI: 10.1001/jama.2014.6095
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Using Tomosynthesis in Combination With Digital Mammography

Abstract: Addition of tomosynthesis to digital mammography was associated with a decrease in recall rate and an increase in cancer detection rate. Further studies are needed to assess the relationship to clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
348
8
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(399 citation statements)
references
References 18 publications
17
348
8
13
Order By: Relevance
“…As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37]. DBT is currently being used in Australia as a diagnostic tool, but there is increasing evidence to suggest that it may be beneficial as a screening tool [33][34][35][36]. However, it is common practice to use DBT in conjunction with, rather than instead of, digital mammography, which results in a total examination dose approximately 2-3 times that of digital mammography alone.…”
Section: Advances In Technologymentioning
confidence: 54%
See 1 more Smart Citation
“…As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37]. DBT is currently being used in Australia as a diagnostic tool, but there is increasing evidence to suggest that it may be beneficial as a screening tool [33][34][35][36]. However, it is common practice to use DBT in conjunction with, rather than instead of, digital mammography, which results in a total examination dose approximately 2-3 times that of digital mammography alone.…”
Section: Advances In Technologymentioning
confidence: 54%
“…The main advantage of DBT is that it significantly reduces the effects of superimposition, thereby enabling visualisation of lesions that would be masked by over-or under-lying tissue and distinguishing real lesions from those mimicked by superimposition of normal structures [29]. A number of studies on large screening populations showed an increase in overall cancer detection rate and a reduction in recall rate when using DBT in addition to 2D digital mammography, compared to using 2D digital mammography alone [33][34][35][36]. As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37].…”
Section: Advances In Technologymentioning
confidence: 99%
“…Newer technology such as digital breast tomosynthesis may provide higher sensitivity and increase cancer detection rate compared with digital mammography because of its ability to remove overlapping glandular tissue, the main reason for both false-positive and -negative results with traditional mammography. [10][11][12][13][14] Although tomosynthesis requires breast compression similar to mammogram, the compression force may be lower without affecting image quality. 14 Further studies would be helpful to determine whether the benefits of the MammoPad used by Chan et al 8 could have further benefit in tomosynthesis.…”
Section: Mammography For Breast Cancer Detection In Hong Kongmentioning
confidence: 99%
“…Digital breast tomosynthesis (DBT) is a three-dimensional imaging technique that may address some of the limitations that DM has, in particular problems related to overlapping tissue. Several recent studies have shown that the combination of DBT and DM improves the cancer detection rate [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%